Mating type‐dependent partner sensing as mediated by VEL1 in Trichoderma reesei. Issue 6 (16th April 2015) - Bazafkan, Hoda; Dattenböck, Christoph; Böhmdorfer, Stefan; Tisch, Doris; Stappler, Eva; Schmoll, Monika
Summary Sexual development in the filamentous model ascomycete Trichoderma reesei (syn. Hypocrea jecorina) was described only a few years ago. In this study, we show a novel role for VELVET in fungi, which links light response, development and secondary metabolism. Vel1 is required for mating in darkness, normal growth and conidiation. In light, vel1 was dispensable for male fertility but essential for female fertility in both mating types. VEL1 impacted regulation of the pheromone system (hpr1, hpr2, hpp1, ppg1) in a mating type‐dependent manner and depending on the mating partner of a given strain. These partner effects only occurred for hpp1 and hpr2, the pheromone precursor and receptor genes associated with the MAT1‐2 mating type and for the mating type gene mat1‐2‐1. Analysis of secondary metabolite patterns secreted by wild type and mutants under asexual and sexual conditions revealed that even in the wild type, the patterns change upon encounter of a mating partner, with again distinct differences for wild type and vel1 mutants. Hence, T. reesei applies a language of pheromones and secondary metabolites to communicate with mating partners and that this communication is at least in part mediated by VEL1.